The degree of transformational leadership practice among university academic leaders at the University of Jordan from the viewpoint of faculty members - Al-Araimi, Jamal Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the degree of transformational leadership practice among university academic leaders at the University of Jordan from the viewpoint of faculty members, and to achieve the goal of the study, the researcher used the descriptive approach, and the tool was represented in a questionnaire distributed to a random sample of (370) faculty members, Where the study population consisted of all faculty members at the University of Jordan, who numbered (1480), the results showed that the total degree of transformational leadership practice at the University of Jordan was obtained from the viewpoint of faculty members at a general average of (2.35) and a large degree, and at the level of axes, a focus has occurred the influence For the ideal (charisma) at the highest average (2.46), followed by the axis of inspirational motivation with an average of (2.37), then the axis of individual considerations with an average of (2.33), and finally the axis of intellectual arousal with an average of (2.21), in addition to that no significant differences emerged in the degree of The practice of transformational leadership is attributed to the variable (gender, and the college), while there are statistically significant differences attributed to the variable of experience and came in favor of the category (10 years or more), and in light of the results a number of recommendations and proposals were presented and the most important of which was the training of university academic leaders on modern administrative methods.